Exploring water quality management with a socio-hydrological model: A case study from Burkina Faso - Carr, Gemma; Barendrecht, Marlies; Balana, Bedru; Debevec, Liza (Informa UK Limited, 2022)
Models that can integrate aspects of society such as institutions, perceptions and behaviours with aspects of the natural system such as rainfall, runoff and water quality may help understand and manage complex human-water systems. In this paper, a socio-hydrological model is developed for the Black Volta (Mouhoun) watershed in Burkina Faso. The model captures the relationships between the awareness to water quality issues and capacity of local organizations, land use in the riparian zone, agricultural practices and suspended sediment concentration as an indicator of water quality. Scenarios are generated for the current situation and for plausible pathways to achieve improved water quality through different riparian land management strategies. Scenario comparison show how water quality improvements are generated if institutional support, resources and capacity of local level organizations are substantially increased compared to current levels.